Peningkatan Keterampilan Menulis Narasi Sejarah dan Budaya Melalui Model Mind Mapping pada Mahasiswa Sejarah dan Kebudayaan Islam UIN Alauddin Makassar - Syamhari, Syamhari; Mundzir, Chaerul (Universitas Islam Negeri Alauddin Makassar, 2021)
Abstract: This research aims to describe the use of the mind mapping model in the skills of writing historical and cultural narratives for students in semester VI AK 3-4, Department of Islamic History and Culture, UIN Alauddin Makassar. The results of the research obtained are that the use of the mind mapping model can improve students' skills in writing historical and cultural narratives as described below: The results of implementing learning using the mind mapping model obtained in implementing this learning are: in cycle one, the content of ideas there is a very high value gain. good 5 percent while in the second cycle the student achievement reached 55 percent in the very good category. The content organization achieved by students in the first cycle was 13 percent in the very good category while in the second cycle it reached 66 percent in the very good category. Meanwhile, the results of the test for the ability to choose words or diction in the very good category in cycle one were 10.5 percent, while in cycle two it increased to 71 percent which received the very good category. Then the results of the structure and vocabulary choice test in writing historical and cultural narratives in cycle one reached 18.42 percent and in cycle two it rose to 76 percent in the very good category, the results of the spelling and grammar test in cycle one were in the very good category, there was a gain of 13 percent while in cycle two it rose to 71 percent. Apart from that, the results of this research show that the use of the mind mapping model can improve the writing skills of sixth semester students of the Islamic History and Culture Study Program, Faculty of Adab and Humanities, UIN Alauddin Makassar in writing historical and cultural narrative paragraphs. Keywords: Islamic History; Culture; Mind Mapping